2003
DOI: 10.1179/joc.2003.15.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Capillary Leak Syndrome Resulting from Gemcitabine Treatment in Renal Cell Carcinoma: A Case Report

Abstract: In a few cases, gemcitabine (GCB) has been shown to result in systemic capillary leak syndrome (SCLS) in the treatment of non-small cell lung, pancreatic, and ovarian carcinomas. SCLS is a life-threatening condition characterized by increased capillary permeability resulting in manifest pulmonary and peripheral edema. Usually SCLS responds successfully to corticosteroid therapy and diuretics. We present a case where GCB treatment likely resulted in SCLS in a male patient with metastatic renal cell carcinoma (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…However, the severity of such a complication, and the hypothesis that cases of peripheral oedema previously related to gemcitabine toxicity might be due to mild forms of capillary leak syndrome, make a case for careful checking of such toxicity in patients receiving gemcitabine 11 . The treatment of this latter complication relies on diuretics and high‐dose corticosteroids 19,21–23 . Gemcitabine cutaneous toxicity has been scarcely reported in the literature.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, the severity of such a complication, and the hypothesis that cases of peripheral oedema previously related to gemcitabine toxicity might be due to mild forms of capillary leak syndrome, make a case for careful checking of such toxicity in patients receiving gemcitabine 11 . The treatment of this latter complication relies on diuretics and high‐dose corticosteroids 19,21–23 . Gemcitabine cutaneous toxicity has been scarcely reported in the literature.…”
Section: Discussionmentioning
confidence: 79%
“…In other neoplastic diseases, haemolytic–uraemic syndrome was previously observed with gemcitabine usually arising after long‐term treatment, and showing reversibility after treatment cessation 14–17 . On the other hand, few studies reported capillary leak syndrome associated with gemcitabine, and up to now it has never been reported in patients with CTCL 18–22 . However, the severity of such a complication, and the hypothesis that cases of peripheral oedema previously related to gemcitabine toxicity might be due to mild forms of capillary leak syndrome, make a case for careful checking of such toxicity in patients receiving gemcitabine 11 .…”
Section: Discussionmentioning
confidence: 99%
“…This acute toxicity was not observed in the control group, in the group G8 and in the remaining animals of the group G12 subsequently treated with 8 mg?kg -1 . Thus, an acute toxicity of aerosolised gemcitabine was suspected in these three animals and compared with that described in isolated cases in the literature after systemic infusion of gemcitabine [14,15]. However, the current study was not designed to compare the pulmonary safety profile of gemcitabine via aerosol and via systemic administration.…”
Section: Tumour Growthmentioning
confidence: 99%
“…The pathophysiology of the damage is not known. A predictor, although a little sensitive, of capillary leak syndrome is the decrease of albumin [11]. This syndrome was described after snake bites [12] in patients with sepsis [13,14] and in patients treated with interleukin-2 [15] and taxotere [16].…”
Section: Discussionmentioning
confidence: 99%